MAKNA GAYA BAHASA PERSONIFIKASI DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA - Erlina Zahar; Devi Syahfitri (Universitas Batanghari, 2019)
The purpose of this research to describe the personification figurative language in the novel Tenggelamnya Kapal Van Der Wijck by Hamka”. There are many kinds of personification in the novel Tenggelamnya Kapal Van Der Wijck by Hamka. The data of this research is primary data in a form of utterances which have personification figurative language in the novel Tenggelamnya Kapal Van Der Wijck by Hamka. The source of the data is the novel Tenggelamnya Kapal Van Der Wijck by Hamka. This research is qualitative by using content analysis. By collecting whola data, choosing, then analyzing the data, the personification figurative language in the novel Tenggelamnya Kapal Van Der Wijck by Hamka can be understood. The researcher then interprets the data in the forms of utterances in the novel. From the analysis, it can be concluded that the personification in the novel Tenggelamnya Kapal Van Der Wijck by Hamka consists of personification which can be seen from the words ombak, tenang, hidup, senja, makan, angin, jembatan